Atomic‐Scale Study of Metal–Oxide Interfaces and Magnetoelastic Coupling in Self‐Assembled Epitaxial Vertically Aligned Magnetic Nanocomposites. Issue 17 (8th July 2019) - Radtke, Guillaume; Hennes, Marcel; Bugnet, Matthieu; Ramasse, Quentin M.; Weng, Xiaorong; Demaille, Dominique; Gobaut, Benoit; Ohresser, Philippe; Otero, Edwige; Choueikani, Fadi; Juhin, Amélie; Sainctavit, Philippe; et al.
Abstract: Vertically aligned nanocomposites (VANs) of metal/oxide type have recently emerged as a novel class of heterostructures with great scientific and technological potential in the fields of nanomagnetism, multiferroism, and catalysis. One of the salient features of these hybrid materials is their huge vertical metal/oxide interface, which plays a key role in determining the final magnetic and/or transport properties of the composite structure. However, in contrast to their well‐studied planar counterparts, detailed information on the structural features of vertical interfaces encountered in VANs is scarce. In this work, high resolution scanning transmission electron microscopy (STEM) and electron energy‐loss spectroscopy (EELS) are used to provide an element selective atomic‐scale analysis of the interface in a composite consisting of ultrathin, self‐assembled Ni nanowires, vertically epitaxied in a SrTiO3 /SrTiO3 (001) matrix. Spectroscopic EELS measurements evidence rather sharp interfaces (6–7 Å) with the creation of metallic NiTi bonds and the absence of nickel oxide formation is confirmed by X‐ray absorption spectroscopy measurements. The presence of these well‐defined phase boundaries, combined with a large lattice mismatch between the oxide and metallic species, gives rise to pronounced magnetoelastic effects. Self‐assembled columnar Ni:SrTiO3 composites thus appear as ideal model systems to explore vertical strain engineering in metal/oxide nanostructures. Abstract : The vertical heterointerface between Ni nanowires and a SrTiO3 matrix in a magnetic composite system is studied at the atomic scale with element selectivity using high resolution scanning transmission electron microscopy and electron energy‐loss spectroscopy. The results indicate the creation of metallic Ni‐Ti bonds and the absence of nickel oxide formation, the latter being confirmed by X‐ray absorption spectroscopy measurements.